San Ireneo y la doctrina de la reconciliación - Orbe, Antonio (Gregorianum, 1980)
The doctrine of the reconciliation, not directly challenged by St. Irenaeus' adversaries, has been left simply unmentioned by scholars. Is this right? I. Irenaeus sketches his ideology in treating Col 21,21 f (adv. haer. V, 14,2-3). In order to explain it by contrast, he had to set forth the heterodox exegesis of the two most significant texts of the Apostle (Eph 2, 13 ff. and Col 1,20 ff): the evident exegesis of Marcion, and that which from analogy was very probably that of the Valentinians. Confronting them, Irenaeus felt obliged to insist on the reconciliation by the Lord's death in a carnal body: not in a merely mystical body (against Marcion), nor in flesh which was sui generis (against the Valentinians). II. There were two reconciliations: the prior with Christ, on the basis of the Incarnation; and the definitive with God the Father, by means of the death on the cross. III. To the reconciliation of Adam (and his descendants) — in his person — according to the obvious bearing of the Pauline formulae, Irenaeus preferred his reconciliation in his nature, according to the flesh. The righteous flesh of the Lord reconciled with God the sinful flesh of Adam (and his descendants). The passages of the Saint submitted to analysis — especially a page of adv. haer. IV, 20,2; and the expressions in the neuter reiterated with the same slant in books III and V with reference to the "lost sheep" — confirm the continuity and coherence of his ideology. He is attentive always to make the human plasma (or caro) the object of the reconciliation, and Christ's carnal body the immediate agent of the same. IV. For his conception Irenaeus does not rest directly on passages of the Apostle or of the N.T. He brings to bear the principles of his anthropology, the biblical definition of man: a body of dust, fashioned in the image and likeness of God. Since the plasma was already man, before being animated by the breath of life, it was constituted protagonist in the economy of salvation. Far from the body's having its being by reason of the soul, according to the pagan conception, the soul — by its being rational and free — served the body in its task of assimilating itself to the Spirit. Therefore the soul does not sin with the aid of the body, but the reverse occurs: the body sins through the ministry of the soul. In Adam it was the plasma which sinned; and in Christ equally it was the plasma, "his body of flesh", which worked the reconciliation. It was not the person of Adam which went astray, but the nature (or earthly substance) which constituted him a man. Nor, consequently, was the reconciliation wrought by the person of the Son, but by his flesh crucified and put to death.